2021
DOI: 10.3390/ijerph19010208
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on the Learning Outcomes of Medical Students in Taiwan: A Two-Year Prospective Cohort Study of OSCE Performance

Abstract: Background/Aims: To avoid the negative impacts of the COVID-19 pandemic on clinical clerkship, supplemental teachings such as digital materials in the scenario-based distal simulations were implemented. This study utilized the OSCE (objective-structured clinical examination) to evaluate the impact of COVID-19 pandemic on the learning outcome of medical students from the regular group (class of 2020) and pandemic-impacted group (class of 2021). Methods: All medical students serially took, firstly, the mock-OSCE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…16 Clinical learning was negatively affected by the pandemic despite online clinical placement implemented to maintain the completeness of clerkship according to a study conducted in Taiwan. 17 However, there are limitations in this study. The first one being the use of purposive sampling along with small sample size, because of which our study is generalizable only to the subpopulation but not on interns working all over the country.…”
Section: Discussionmentioning
confidence: 86%
“…16 Clinical learning was negatively affected by the pandemic despite online clinical placement implemented to maintain the completeness of clerkship according to a study conducted in Taiwan. 17 However, there are limitations in this study. The first one being the use of purposive sampling along with small sample size, because of which our study is generalizable only to the subpopulation but not on interns working all over the country.…”
Section: Discussionmentioning
confidence: 86%
“…Although the focus of university learning centres on the acquisition of theory and knowledge, the development of practical skills is a vital aspect of learning given the nature of their respective healthcare roles. Previous research using OSCE (objective-structured clinical examination) reported the pandemic hampered learning outcomes among final year medical students in their clinical preparation [ 18 ]. Other research has suggested an increased need to counterbalance the lack of clinical experience with virtual or simulated learning [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clerkships, students are assigned to various departments, including internal medicine, surgical disciplines, pediatrics and emergency medicine. They acquire clinical knowledge by shadowing and assisting residential physicians in daily practice, primary patient care, bedside procedures, daily record writing and case presentations (11). The pandemic challenged the educational and healthcare system worldwide.…”
Section: Discussionmentioning
confidence: 99%